Analysis of the Success of the BSI Mobile Service Information System Among Generation Z Using the DeLone and McLean Method - Rista Dwi Jayanti; Yan Putra Timur; Muhammad Rifqi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid growth of digital banking in Indonesia has transformed financial transactions and created an urgent need to evaluate the success of mobile banking systems. This study investigates the success of the Bank Syariah Indonesia (BSI) Mobile information system among Generation Z users by applying the DeLone and McLean model, which includes six key dimensions: system quality, information quality, service quality, system use, user satisfaction, and net benefits. A quantitative approach was employed using an online survey of 96 Generation Z respondents who actively used BSI Mobile for at least three months. Data were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that information quality significantly influences system use, while service quality significantly affects user satisfaction. Furthermore, system use positively impacts both user satisfaction and net benefits, and user satisfaction shows the strongest effect on net benefits. In contrast, system quality has no significant relationship with system use or user satisfaction, and information quality does not demonstrate a significant effect on user satisfaction. These results provide practical implications for Bank Syariah Indonesia to enhance digital service quality and strengthen Generation Z engagement, as well as theoretical contributions by validating the DeLone and McLean model in the context of Islamic mobile banking.